2021
DOI: 10.3390/jcm10215171
|View full text |Cite
|
Sign up to set email alerts
|

Can Dog-Assisted Intervention Decrease Anxiety Level and Autonomic Agitation in Patients with Anxiety Disorders?

Abstract: Few studies have explored the influence of an Animal-Assisted Intervention on patients with mental disorders. We investigated it’s impact on anxiety symptoms. We divided 51 patients with anxiety symptoms into two groups—treatment group, that went for a short 15–20 min’ walk with a dog, his handler and a researcher and control group, that went for a walk only with a researcher. We used State-Trait Anxiety Inventory (STAI), Visual Analogue Scale (VAS) of fear, Beck Depression Inventory (BDI), Ford Insomnia Respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Actually, whether this physiological response is indicative of positive excitement or of potentially negative stress remains an open question. However, the observed positive effect (i.e., reduction) on systolic and diastolic blood pressure would seem to corroborate the hypothesis that human–animal interactions could contribute to improve the functioning of the cardiovascular system [ 33 , 34 , 35 , 36 , 37 ].…”
Section: Resultssupporting
confidence: 52%
“…Actually, whether this physiological response is indicative of positive excitement or of potentially negative stress remains an open question. However, the observed positive effect (i.e., reduction) on systolic and diastolic blood pressure would seem to corroborate the hypothesis that human–animal interactions could contribute to improve the functioning of the cardiovascular system [ 33 , 34 , 35 , 36 , 37 ].…”
Section: Resultssupporting
confidence: 52%
“…In the category “animal,” we included studies that had an experimental condition with a live animal and that compared that condition to a control condition with no animal present (e.g., Julius et al, 2013 ; Kim et al, 2016 ; Branson et al, 2017 ; Hartfiel et al, 2017 ; Levinson et al, 2017 ; Schuck et al, 2018 ; Wolynczyk-Gmaj et al, 2021 ; Abdel-Aziem et al, 2022 ). We found that 88.37% ( n = 152) of the studies controlled for an animal as a specific factor.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a systematic review [137] reported a significant reduction in heart rate, blood pressure, and/or cholesterol levels in some studies. Individual studies have reported decreased heart [138][139][140][141] and respiratory [138] rates, as well as lowered blood pressure [140] and increased heart-rate variability [139]. AAI-associated neuroendocrine changes (discussed below) are thought to, at least partly, underlie decreased stress and arousal associated with these interventions [126].…”
Section: Transdiagnostic Benefits and Symptom Reductionmentioning
confidence: 99%